Using Natural Language Processing and Artificial Intelligence to Explore the Nutrition and Sustainability of Recipes and Food - van Erp, Marieke; Reynolds, Christian; Maynard, Diana; Starke, Alain; Ibáñez Martín, Rebeca; Andres, Frederic; Leite, Maria C. A.; Alvarez de Toledo, Damien; Schmidt Rivera, Ximena; Trattner, Christoph; Brewer, Steven; Adriano Martins, Carla; et al. (Frontiers in Artificial Intelligence, 2021)
In this paper, we discuss the use of natural language processing (NLP) and artificial intelligence (AI) to analyse nutritional and sustainability aspects of recipes and food. We present the state of the art and some use cases, followed by a discussion of challenges. Our perspective on addressing these is that while they typically have a technical nature, they nevertheless require an interdisciplinary approach combining NLP and AI with expert domain knowledge to create practical tools and comprehensive analysis for the food domain.